Angiotensin I–converting enzyme–inhibitory peptides from bovine collagen: insights into inhibitory mechanism and transepithelial transport. (November 2016) - Fu, Yu; Young, Jette Feveile; Rasmussen, Martin Krøyer; Dalsgaard, Trine Kastrup; Lametsch, René; Aluko, Rotimi E.; Therkildsen, Margrethe
Abstract: The inhibitory mechanism and transepithelial transport of angiotensin I-converting enzyme (ACE)-inhibitory peptides (VGPV and GPRGF) derived from Alcalase®- and papain-hydrolyzed bovine collagen were investigated. The inhibitory mechanism of VGPV and GPRGF was experimentally determined to be non-competitive and the results were supported by molecular docking data. In silico and in vitro gastrointestinal digestion indicated that VGPV remained resistant to digestive enzymes, while GPRGF was degraded into smaller ACE-inhibitory peptides (GPR and GF). VGPV and GPRGF were transported across monolayers of human intestinal epithelial Caco-2 cells through paracellular pathway and retained their ACE-inhibitory activities. The present study suggests that VGPV and GPRGF may possibly be absorbed and exert antihypertensive effects in vivo . Graphic abstract: Highlights: A novel collagen-derived ACE-inhibitory peptide was identified. VGPV and GPRGF remained stable towards digestive enzymes. Collagen-derived ACE-inhibitory peptides were non-competitive inhibitors. VGPV and GPRGF were transported across Caco-2 cell monolayers via the paracellular pathway.